INSIDENSI PENYAKIT KERDIL (Bunchy top virus) PADA TANAMAN PISANG (Musa paradisiaca L) DI KECAMATAN AER TEMBAGA KOTA BITUNG - Sasmita Mokolintad; Redsway Maramis; Henny Makal (COCOS, 2021)
ABSTRACTBanana (Musa paradisiaca L) is a commodity that is quite attractive to be developed andincreased its production, if it is viewed from the aspect of International trade. Indonesia is acountry is ranked sixth out of the to ten Banana producers in the world and accounts for around30% of domestic fruit production. Banana plants can grow well in low and high areas with analtitude of not more than 1600m above sea level. Many factors can inhibit plant growth,including disease attacks. Some Banana cuktivars that have been released are infected with theBunchy Top Virus. This study aims to determine the Incidence of Bunchy Top Virus attack onBanana plants in Bitung City, Aer Tembaga District, which is located in three villages, namely inKasawari Village, Makawidey Village, and Tandurusa Village. This research was carried out forthree from October to December 2018. This research was conducted by survey method or directobservation at the research location. The results of research on the Incidence of BananaBunchyTop Virus in Bitung city, Aer Tembaga sub-district in three villages. The highest averageIncidence of dwarf disease was in Makawidey villages 11,3%, followed by Tandurusa villages at10,6% then the ;owest Incidence occurred in Kasawari villages 3,45%.